Zanzibar - The Effect of the Investment Climate on Performance of Micro and Small Enterprise in Zanzibar : A Comparison with Mainland Tanzania and Other Countries - World Bank (Washington, DC, 2012)
This study looks at firm performance and the investment climate in Zanzibar. The main source of information is a 2003-2004 survey of manufacturing enterprises. The report is complementary to an earlier report looking at the investment climate in the whole of the United Republic of Tanzania, including Zanzibar (Regional Program on Enterprise Development, 2004). To avoid redundancy with the earlier report, this report focuses on areas where the investment climate is different in Zanzibar from mainland Tanzania. Zanzibar is a small island economy found close to the Tanzanian mainland. Like other small island economies, limited diversification and a small domestic market make Zanzibar vulnerable to terms of trade and other shocks. Diversifying into manufacturing a goal that is consistent with Zanzibar's Growth Strategy (2006-2015) would reduce this vulnerability. This report looks at existing manufacturing firms in Zanzibar to see how their performance compares with similar firms in other parts of Tanzania, other countries in Africa, and other small island economies. It also compares the investment climate in Zanzibar with the investment climate on the mainland and in other nearby countries. Although the investment climate in Zanzibar is more favorable in many areas than it is on the mainland, firms remained more concerned about several areas. Consistent with the evidence on worker skills and capital intensity, firms were more likely to say that access to finance and workers skills and education were serious problems than firms on the mainland were. Objective data are consistent with this-fewer firms had loans, firms reported having less capital and workers and managers were less likely to be university educated in Zanzibar. Improving education and taking steps to attract skilled workers from the mainland and elsewhere -- and improving access to finance, therefore, should be a priority.